Pengembangan Ekonomi Kreatif Produk Batik Gandusari Melalui Green Marketing Menuju Industri Ramah Lingkungan - Wuryan Andayani; Endra Yuafanedi Arifianto; Sri Wardhani; Edriana Pangestuti; Sri Palupi Prabandari (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
Batik Nimas Sekarsari, a small business located in Gandusari, Blitar Regency, faces several challenges regarding financial accounting, Cost of Goods Sold (COGS) determination, profit calculation, and financial management. Additionally, the business encounters marketing limitations, with its reach currently restricted to the Blitar Regency area. To address these issues, comprehensive assistance and mentoring were required. The methods employed included training sessions on financial accounting, COGS determination, profit calculation, investment strategies, and financial management. Furthermore, Human Resource (HR) development was enhanced by training the partners in digital catalog creation and Instagram marketing. The results indicate that the utilization of Instagram marketing significantly expanded the business's market reach. Monitoring and evaluation demonstrated that following the training and mentoring sessions, the partner experienced a profit increase of approximately 20%. This Doctoral Service Program (Doktor Mengabdi) contributes to several key areas: 1) Supporting the Sustainable Development Goals (SDGs), specifically "No Poverty," by fostering rural economic independence through batik entrepreneurship; 2) Implementing the Universitas Brawijaya Community Service Strategic Plan (RENSTRA) 2021–2025 concerning Community Empowerment; 3) Strengthening Social and Economic Resilience through MSME development, local economic capacity building, and cultural preservation; 4) Achieving Key Performance Indicator (IKU) 2 by providing students with off-campus experience (recognized as a 4-credit PKM); 5) Fulfilling IKU 3 through lecturers' off-campus activities; and 6) Establishing business management certainty, strengthening product branding, and expanding the reach of eco-friendly green marketing.